1997
DOI: 10.1063/1.474242
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the temperature dependence of dielectric relaxation in liquid water by THz reflection spectroscopy and molecular dynamics simulation

Abstract: We report measurements of the real and imaginary part of the dielectric constant of liquid water in the far-infrared region from 0.1 to 2.0 THz in a temperature range from 271.1 to 366.7 K. The data have been obtained with the use of THz time domain reflection spectroscopy, utilizing ultrashort electromagnetic pulses generated from a photoconductive antenna driven by femtosecond laser pulses. A Debye model with an additional relaxation time is used to fit the frequency dependence of the complex dielectric cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
355
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(408 citation statements)
references
References 65 publications
44
355
2
1
Order By: Relevance
“…20,21,22,23,24 There is also abundant literature on the low-frequency spectral response of water between a few wavenumbers and the O···O stretching vibration ν O···O . 25,26,27,28,29,30 Static x-ray spectroscopy experiments have been used to investigate the oxygen K-edge of water, the near-edge region of which is shown in Fig. 1B.…”
Section: Introductionmentioning
confidence: 99%
“…20,21,22,23,24 There is also abundant literature on the low-frequency spectral response of water between a few wavenumbers and the O···O stretching vibration ν O···O . 25,26,27,28,29,30 Static x-ray spectroscopy experiments have been used to investigate the oxygen K-edge of water, the near-edge region of which is shown in Fig. 1B.…”
Section: Introductionmentioning
confidence: 99%
“…In this spectral region we probe intermolecular collective modes of the hydrogen bond network with periods of 0.45-0.35 ps. Terahertz absorption spectroscopy is known to probe the reorientation of permanent and induced dipole moments (46). The time correlation function of the polarization of bulk water has been described by a biexponential decay with a slow and a fast component with Debye relaxation times of Debye Ͼ 2 ps (attributed to structural relaxation) and Debye Ͼ 50 fs, respectively (47).…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Temperature-dependent IXS studies, in which the density was kept approximately constant to 1 g/cm 3 by changing the pressure, revealed that, as long as τ α remains in the picosecond region (i. e. in the high temperature region), it follows an Arrhenius behavior with an activation energy comparable to the hydrogen bond energy. This result provided a link between the relaxation process and the hydrogen bond network, and offered an explanation for the microscopic origin of the structural relaxation process in water.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, this is done by inelastic scattering techniques using neutrons (INS) or x-rays (IXS), or by molecular dynamics (MD) studies. More recently, the high-frequency dynamics has been studied experimentally by time-domain spectroscopy [3,4]. The key quantity in most of these studies is the so-called dynamical structure factor S(Q, ω) ( Q and ω = E denote the momentum and energy transfer, respectively), which is the time and space Fourier transform of the atomic density-density pair correlation function [5].…”
Section: Introductionmentioning
confidence: 99%